Identifying pregnant and postpartum women's priorities for enhancing nutrition support through social needs programmes in a resource-constrained urban community in South Africa - Agnes Erzse; Chris Desmond; Karen Hofman; Mary Barker; Nicola Joan Christofides (BMC, 2024)
Abstract Background Malnutrition remains a pressing public health concern for mothers and children in South Africa. Despite the government's multisectoral response, unaddressed social needs prevent some mothers getting full benefit from interventions, spanning financial planning, income stability, housing, access to government services, social support, and provision of affordable, nutritious foods. Engaging with mothers and prioritising their concerns is important if we wish to overcome obstacles to women benefiting from government nutrition interventions. This study aimed to identify the programmes that women perceived as a priority in addressing the social needs of mothers of young infants and pregnant women to enhance nutrition in a resource-constrained urban township in South Africa. Methods A cross-sectional study employed a quantitative preference elicitation survey, administered to 210 mothers and pregnant women from five primary healthcare facilities in Soweto. The survey tool was developed with the community to identify unmet social needs and potential solutions, which were synthesised with findings from the literature. The survey described 15 programmes, grouped into three delivery levels: clinics, community, and government. Participants were required to rank programme options in two stages. First, they selected their top two programmes within each delivery level. Subsequently, they allocated stickers to indicate the strength of their preference among the top programmes across the levels. Rankings were analysed using descriptive statistics. Results The highest priority was given to five programmes. Two delivered at the community level: Women's economic empowerment groups and Job search assistance, two at the clinic level: Social needs assessment and referral, and Prescription-based food, and one at the government level: Free quality childcare. The lowest-ranked programmes were two clinic-based programmes, specifically Maternal nutrition groups and Couple antenatal education. Conclusion Women expressed strong views about which programmes should be prioritised to support mothers and pregnant women in addressing their social needs and improving nutrition. Key areas included providing support with job searching and entrepreneurship, accessing childcare and the healthy foods recommended at clinics, as well as finding information on available community and government services. Leveraging multisectoral collaboration, aligned policy objectives, efficient public financing, and strengthened implementation capacity will be pivotal in delivering these programmes.